A hairy situation: Plant species in warm, sunny places are more likely to have pubescent leaves - Angela T. Moles; Shawn W. Laffan; Matthew Keighery; Rhiannon L. Dalrymple; Marianne L. Tindall; Si‐Chong Chen (Journal of Biogeography, 2020)
Aim Leaf pubescence has several important roles, including regulating heat balance, reducing damage from UV radiation, minimizing water loss and reducing herbivory. Each of these functions could affect a plant's ability to tolerate the biotic and abiotic stresses encountered in different parts of the world. However, we know remarkably little about large scale biogeographic patterns in leaf pubescence. Our aims were: (a) to determine whether a higher proportion of species have pubescence at sites where it is hot, dry and solar radiation is high, and (b) to quantify the latitudinal gradient in pubescence. Location Australia. Taxon Vascular land plants. Methods We compiled data on the presence/absence of pubescence on mature photosynthetic organs for 4,183 species, spanning 107 families. We combined these data with over 1.9 million species occurrence records from the Atlas of Living Australia to calculate the proportion of species with pubescence in 3,261 grid cells spanning the Australian continent. Results The proportion of pubescent species was most closely related to solar radiation ( R 2 = 0.33), followed by maximum temperature in the warmest month ( R 2 = 0.30). Mean annual precipitation was very weakly related to pubescence ( R 2 = 0.01). We found a significant negative relationship between latitude and pubescence ( R 2 = 0.19), with the average percentage of species with pubescence dropping from 46% at 10° S to 35% at 44° S. This cross‐species relationship remained significant after accounting for phylogenetic relationships between species. We found that a quadratic model explained more variation in pubescence across latitudes than did a linear model. The quadratic model shows a peak in the proportion of pubescent species at 19° S (within the tropics). Main conclusions Our findings are consistent with the idea that leaf pubescence may have a protective function in areas with high solar radiation and high temperatures. Our data are also consistent with the idea that species towards the tropics should be better defended than are species at higher latitudes.